A POLÍTICA DE COTAS RACIAIS NA UNIVERSIDADE FEDERAL DO MARANHÃO: subjetividade e identidade de estudantes negros cotistas como perspectivas de análise. - FURTADO, Taisa Teresa Gomes (2018)
The policy of racial quotas is characterized as a fundamental affirmative action policy in the correction of inequalities and in the repair of a history of marginalization suffered by the black population through the guarantee of access to higher education. However, as important as its implementation is the assistance and follow-up of these black student quotaters, regarding the effects and subjective implications that the racism experienced in the academic environment can cause. In this sense, the present research aimed to analyze the processes of construction of the subjectivity and identity of black students of the Federal University of Maranhão (UFMA), seeking to identify how racial relations in UFMA occur, demarcating the differences between the higher grade courses to relate the specificities of the difficulties faced by black students and their impact on their self-esteem and self-concept, as well as pointing out the coping strategies used by them against prejudice and racial discrimination. Interviews were conducted with eight students from the highest grade courses at each of the academic units of the University City Campus: Law, Chemical Engineering, Medicine and Psychology. Data analysis was based on the theoretical-methodological framework of Socio-Historical Psychology. The results show that the common difficulties faced by these students are mostly the financial question and the effort to keep pace with the course and other classmates. Black quotations students tend to suffer racial prejudice more explicitly in their relationship with teachers in medical school, and are also prejudiced by the fact that they are quota holders. The coping strategies proposed by them concern the importance of institutional support and groups of the black movement. Moreover, admission to university provided or intensified the recognition of a black identity on the part of quota students.